EC Boys reunion gets bigger - Shahrinnahar, Latib (The New Straits Times Press (M) Bhd., 2018)
After almost 46 years of being separated due to career and work commitments, 30 former Sultan Abu Bakar College students, formerly known as the English College. in Johor Baru met up.